Graphic inquiry - Lamb, Annette C.; Callison, Daniel 1948- (Libraries Unlimited, 2012)
This full-color book provides a practical approach to incorporating graphic inquiry across the curriculum for school library media specialists, technology coordinators, and classroom teachers. We live in a high-tech, multimedia world, and it's proven that many young people respond best to graphic communication, yet most of our classroom activities still emphasize print communication. Even inquiry-based approaches to learning often stress writing lists of questions, reading texts, and writing papers. The potential of graphic inquiry in teaching and learning warrants exploration. It's new. It's graphic. And it is the first of its kind. Designed to bridge theory and actual practice, Graphic Inquiry has applications for new and practicing educators and librarians. This visually rich book provides numerous, standards-based inquiry activities and projects that incorporate traditional materials as well as emerging social and collaborative technologies.